Hirsutella Sinensis Fungus Regulates CD8+ T Cell Exhaustion Through Involvement of T-Bet/Eomes in the Tumor Microenvironment - Jin, Lu; Jin, Lushuai; Wu, Renjie; Liu, Xia; Zhu, Xinhai; Shou, Qiyang; Fu, Huiying (Frontiers in Pharmacology, 2021)
Background: Targeting exhausted T (Tex) cells is a promising strategy for anti-tumour treatment. Previously, we demonstrated that Hirsutella sinensis fungus (HSF) could significantly increase T cell infiltration and the effector T cell ratio in the tumour microenvironment, activating systemic immune responses. However, we do not know how HSF regulates Tex cells in the tumour microenvironment. Here, we explored the mechanism underlying HSF inhibition of Tex cells and tumour growth and metastasis in breast cancer. Methods: We examined the effects of HSF on various tumour mouse models using in vivo imaging technology. Lung metastasis was detected by H&E staining and the T cell subsets in the tumour microenvironment were assayed with flow cytometry. The in vitro proliferation, function and apoptosis of CD8+ T cells were measured, as well as the T-bet and PD-1 mRNA expressions. Results: HSF inhibited tumour growth and lung metastasis in the mice, and had significantly higher CD44LowCD62LHi and CD44HiCD62LLowpopulations in the tumour-infiltrating CD8+ T cells. However, HSF significantly reduced levels of inhibitory receptors, such as PD-1, TIGIT, CTLA-4, and regulatory T cells. In vitro, HSF inhibited the CD8+ T cell apoptosis rate, and promoted CD8+ T cell proliferation and secretion of interferon (IFN)-γ and granzyme B. Furthermore, HSF treatment both in vivo and in vitro significantly increased Eomes expression, while decreasing T-bet expression. Conclusions: HSF exerted anti-tumour effects mainly through the immune system, by promoting effector/memory T cells and reducing Tex cell production in the tumour microenvironment. The specific mechanisms involved inhibiting T-bet and promoting Eomes to decrease the expression of immune inhibitor receptors and enhance the T cell function, respectively.